The cyst-theca relationship of the dinoflagellate cyst Trinovantedinium pallidifulvum, with erection of Protoperidinium lousianensis sp. nov. and their phylogenetic position within the Conica group. (3rd April 2017) - Mertens, Kenneth Neil; Gu, Haifeng; Takano, Yoshihito; Price, Andrea M.; Pospelova, Vera; Bogus, Kara; Versteegh, Gerard J. M.; Marret, Fabienne; Turner, R. Eugene; Rabalais, Nancy N.; Matsuoka, Kazumi
ABSTRACT: We establish the cyst-theca relationship of the dinoflagellate cyst species Trinovantedinium pallidifulvum Matsuoka1987 based on germination experiments of specimens isolated from the Gulf of Mexico. We show that the motile stage is a new species, designated as Protoperidinium louisianensis . We also determine its phylogenetic position based on single-cell polymerase chain reaction (PCR) of a single cell germinated from the Gulf of Mexico cysts. To further refine the phylogeny, we determined the large subunit (LSU) sequence through single-cell PCR of the cyst Selenopemphix undulata isolated from Brentwood Bay (Saanich Inlet, BC, Canada). The phylogeny shows that P. louisianensis is closest to P. shanghaiense, the motile stage of T. applanatum, and is consistent with the monophyly of the genus Trinovantedinium . Selenopemphix undulata belongs to a different clade than Selenopemphix quanta (alleged cyst of P. conicum ), suggesting that the genus Selenopemphix is polyphyletic. Trinovantedinium pallidifulvum is widely distributed with occurrences in the Gulf of Mexico, the North Atlantic, the northeast Pacific and southeast Asia. In addition, we illustrate the two other extant species, Trinovantedinium applanatum and Trinovantedinium variabile, and two morphotypes of Trinovantedinium . Geochemical analyses of the cyst wall of T. pallidifulvum indicate the presence of amide groups in agreement with other heterotrophic dinoflagellate species, although the cyst wall of T. pallidifulvum also includes some unique features.